An investigation of saccharide complexation by aqueous oxoacids. Can oxoacids mediate A1-2 quorum sensing in bacteria? - Vis, Bradley (My University, 2013)
The goal of this investigation was to determine whether it is plausible for bacterial AI-2 quorum sensing to be selectively regulated by environmentally available oxoacids. In particular, we investigated the ability of H2CO3 and H4SiO4 to bind molecules structurally analogous to the AI-2 signaling compound (a hydration product of (4S)-4,5-dihydroxy-2,3-pentanedione, S-DPD) which is known to be bound to H3BO3 in the AI-2 receptor site of V. harveyi. We report the first ever evidence of mono- and di-ester linked complexes formed spontaneously between carbonic acid and aqueous polyhydroxy hydrocarbons, providing support for the hypothesis that a complex between H2CO3 and some S-DPD derivative regulates AI-2 quorum sensing in S. gordonii. The carbonate centre in these novel complexes retains three-fold coordination. Additionally, we compared the binding affinity of silicic acid to that of boric acid and carbonic acid to several different alcohols and saccharides, and determined that the formation constants generally increase as H2CO3 < H4SiO4 < H3BO3. It seems entirely plausible, therefore, that silicic acid could modulate AI-2 quorum sensing in Sirich environments such as soil solutions. Finally, we determined that stannic acid is also complexed by a range of polyhydroxy hydrocarbons in aqueous solution and characterized of structures of many of the resulting mono-, bis- and tris-ligand complexes.
Keywords: A1-2 quorum sensing; Saccharide complexation; Aqueous oxoacids